TYMS presents a novel biomarker for diagnosis and prognosis in patients with pancreatic cancer - Fu, Zhuo; Jiao, Yan; Li, Yanqing; Ji, Bai; Jia, Baoxing; Liu, Bin (Medicine (Baltimore), 2019)
Pancreatic cancer is one of the most malignant tumors worldwide. DNA replication plays a critical role in the occurrence and development of pancreatic cancer. TYMS encodes thymidylate synthase, which is important for DNA synthesis. The TYMS gene has been assessed in some tumors. However, the specific role of TYMS in pancreatic cancer has not been identified. This study was designed to clarify the diagnostic and prognostic significance of TYMS in pancreatic cancer.The Cancer Genome Atlas (TCGA) database was used to compare TYMS expression in pancreatic cancer, and ROC curve analysis was used to investigate its diagnostic value. The correlation between clinical characteristics and TYMS expression was analyzed, and the prognostic value of TYMS expression in the patients with pancreatic cancer was assessed by Kaplan-Meier curves and Cox analysis.TYMS was upregulated in pancreatic cancer and associated with poor overall survival (OS) and recurrence-free survival (RFS). Univariate and multivariate survival analysis demonstrated that TYMS is an independent risk factor for OS and RFS in patients with pancreatic cancer.The upregulation of TYMS in pancreatic cancer leads to unfavorable OS and RFS in patients, and represents a diagnostic and prognostic biomarker for patients with pancreatic cancer.